Articulation Speaks to Executive Function: An Investigation in 4- to 6-Year-Olds - Netelenbos, Nicole; Gibb, Robbin L.; Li, Fangfang; Gonzalez, Claudia L. R. (Frontiers in Psychology, 2018)
Executive function and language learning play a prominent role in early childhood development. Empirical research continues to point to a concurrent relation between these two faculties. What has been given little attention however, is the association between executive function and speech articulation abilities in children. This study investigated this relation in children aged 4-6 years. Significant correlations indicated that children with better executive function (via parental report of the BRIEF inventory) exhibited stronger speech sound production abilities in the articulation of the “s” and “sh” sounds. Furthermore, regression analyses revealed that the Global Executive Composite (GEC) of executive function as measured by the BRIEF, served as a predictor for speech sound proficiency and that speech sound proficiency served as a predictor for the GEC. Together, these results demonstrate the imbricated nature of executive function and speech sound production while bearing theoretical and practical implications. From a theoretical standpoint, the close link between executive function and speech articulation may indicate a common ontogenetic pathway. From a practical perspective, the results suggest that children with speech difficulties could be at higher risk for executive function deficits.